DAKWAH TEORI, DEFINISI DAN MACAMNYA - Dalinur M. Nur (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
The dynamics of community life continues to evolve. the missionary activity should be dynamic, innovative, and creative. Location of propagation dynamics and creativity, not only on material that should always be relevant to the needs of the community (mad'u) but also in theory.Methodology, and the media used. In addition, the mission also need to use a variety of theoretical footing, good communication theory, psychology, and sociological theory.Even more so. The phenomenon of propagation of Islam is a big challenge and play like how to describe and analyze the principles of Islam is universal-expressed in a social context that is different. Diverse expressions of Islam that it shows that there is a process of continuous dialong between normative Islam and Islam is a dynamicProphet Muhammad peace be upon him, has provided a frame of mind as the principles and methodology of propagation systems empirically with his saying: khatibu Anas al-'alaqadri' aqulihim. Preaching in accordance with the level of thinking mad'u way of thinking is reflected and reflected in the system of human life: the way of belief, culture, society, and civilization.Therefore, a successful mission is the mission carried out with the knowledge and wisdom. By understanding all the issues that arise from the interaction of the elements of a scientific mission.Explanatory system is obtained for all the propaganda and the realities and problems solving methodology.